2020
DOI: 10.2147/idr.s277477
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Determinants of Multidrug-Resistant Tuberculosis in Makkah, Saudi Arabia</p>

Abstract: Background and Objectives Tuberculosis (TB) is a global public health issue. The emergence of multidrug-resistant (MDR) TB has further complicated the situation in the form of poor treatment outcomes and costs to individuals and health-care systems. We therefore aimed to measure the prevalence and associated risk factors of MDR TB among TB patients in Makkah city. Patients and Methods This was a cross-sectional study conducted at Al-Noor Specialist Hospital, a public-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
2
24
1
2
Order By: Relevance
“…With regard to Makkah, only one study thus far has endeavored to examine the prevalence and determinants of MDR-TB [ 13 ]. This study was a single-center experience from the Al-Noor Specialist Hospital, reporting only a total of 158 patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to Makkah, only one study thus far has endeavored to examine the prevalence and determinants of MDR-TB [ 13 ]. This study was a single-center experience from the Al-Noor Specialist Hospital, reporting only a total of 158 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a single-center experience from the Al-Noor Specialist Hospital, reporting only a total of 158 patients. This study revealed that the prevalence rate of MDR-TB was 5% [ 13 ]. Moreover, this study demonstrated that age, lung disease, and a previous history of TB were substantial factors correlated with MDR-TB [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations